Improving Fine Motor Skills Through Handicraft Activities in Kindergarten Group B - Salbiah Agustini; Muhammad Yusuf; Uswatun Nisa; Herman Taufik (CV. Edujavare Publishing, 2025)
This classroom action research aimed to improve fine motor skills in children aged 5–6 years old in Group B TK ABA Rahmaniah Banjarbaru through a series of structured handicraft activities. The research was motivated by the observation that most children exhibited underdeveloped fine motor skills, which are essential for daily functioning and school readiness. The intervention consisted of two cycles, each with three sessions, where children created pencil holders from recycled plastic bottles, engaging in cutting, gluing, coloring, and decorating. Data were collected through observation checklists, documentation, and descriptive analysis. The results revealed a significant improvement: children in the